Practitioner-Based Theory Building in Organizational Ethics - Nielsen, R. P. (Journal of business ethics, 2010)
Understanding of organizational ethics phenomena requires complex understanding of organizational practices in their real world contexts. We can try to understand and build theory about these complex real world practices from the points of view of: (1) a traditional deductive, ethics literature-based, literature gap formulation approach; or, (2) an inductive, practitioner-based literature gap formulation approach. This consideration of inductive, practitioner-based versus deductive, literature-based literature gap formulation is related to the discussion concerning “engaged scholarship” and relationships and gaps between theory and practice in organization studies [Van De Ven, 2007, Engaged Scholarship: A Guide for Organizational and Research Knowledge (Oxford University Press, NY)]. However, there is an important difference with respect to the key issue of ethics literature versus practitioner-based literature gap formulation. This article offers examples of the two different approaches and makes comparisons between them. Implications for practice-based organizational ethics theory building, Ph.D. education, and public intellectual work are considered.